Penggunaan Media Sosial sebagai Strategi Promosi Pariwisata untuk Meningkatkan Kunjungan Wisatawan di Pantai Gope, Banten - Siregar, Herlina; Pertiwi, Fitri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
The tourism sector in Serang City, especially at Gope Beach, is experiencing significant challenges such as a decrease in visits due to the Covid-19 pandemic and natural disasters. Even though there is rich tourism potential, the use of social media for promotion is still very minimal, resulting in a lack of information about tourist attractions to the public. The outreach program designed to increase public understanding of the use of social media in promoting tourism is expected to create greater attraction for tourists. Methods that involve active participation from the community, education, including marketing strategies on social media, show positive results with increased community enthusiasm. The activity involved 15 participants, consisting of fishermen and traders around Gope Beach. Through this activity, participants gained knowledge about the importance of utilizing social media a a means of tourism promotion and the ability to use social media to create simple content related t the attractions of Gope Beach.